Folk Medicine at the Margins of Ethnological Interest - Đaković, Branko; Bukovčan, Tanja (2007)
Folk medicine, commonly also called traditional medicine, has been in recent anthropological research discussed and analyzed under the framework of complementary and alternative medical practices, as one of the ‘ Other’ medicines opposing to the paradigmatic determinism of conventional, Western, medicine. However, in the past ethnological researches in the region of Southeastern Europe, there were some attempts to document and salvage medical knowledge and practices of rural population, never as a specific topic or object of research, but always as a part of research on customs and beliefs, rituals, religious and magical practices or part of folkloristic researches dealing with verbal formula used in different healing and/or preventive practices. The aim of this presentation is to show in which ways did these collections of medicinal knowledge, real cook-books of medical recipes, called ljekaruše, organize knowledge on body, health, illness and culture.
Projekt MZOS
ENG